Pengaruh Sales Growth, Tax Planning, dan Ukuran Perusahaan Terhadap Manajemen Laba (Studi Empiris pada Perusahaan Manufaktur Sektor Industri Dasar dan Kimia yang terdaftar di Bursa Efek Indonesia tahun 2019-2021) - Handa Riska, Lidya; Syafitri, Yulia; Yani, Meri (Ekasakti Pareso Jurnal Akuntansi, 2024)
Earnings Management is the process of taking certain deliberate steps within the limits of generally accepted accounting principles to produce the desired level of reported profits. The data used in this research is secondary data from financial report data of Basic Manufacturing and Chemical companies listed on the Indonesia Stock Exchange. The sample in this study consisted of 13 companies that were consistent in reporting financial reports and had been selected using several sample observation criteria. The sample selection method is using purposive sampling, namely a sampling method with certain criteria. The analytical method used is Multiple Linear Analysis and Coefficient of Determination. The hypothesis testing method in this research uses the t-test and F-test. The results of this research show that the Sales Growth variable shows a t-count value of 1.783. The significance level shows 0.005 which is smaller than the significance level of 0.004. This means that H1 is accepted and it can be concluded that Sales Growth independently has a significant effect on Profit Management.